Social Network Analysis and Social Work Inquiry - Gillieatt, Sue; Fernandes, Christina; Fielding, Angela; Hendrick, Antonia; Martin, Robyn; Matthews, S. (Routledge, 2015)
Understanding and positively impacting social networks is core to social work practice and research. As a research method, social network analysis provides an important mechanism for mapping various types of networks as well as the relationships and exchanges between network actors. This has relevance to Australian human and health services given the social policy context that currently emphasises and requires improvements in the integration of services. This paper describes the application of social network analysis to a consortium of mental health and related services to examine indicators of service integration such as the frequency, type, and direction of information exchanges including referral pathways. When combined with other research methods and information, social network analysis is shown to be a useful tool providing both visual and sociometric evidence of relational activities, thus creating a strong basis for advocacy and social change.